2012
DOI: 10.1016/j.febslet.2012.09.019
|View full text |Cite
|
Sign up to set email alerts
|

[NiFe]‐hydrogenase maturation: Isolation of a HypC–HypD complex carrying diatomic CO and CN ligands

Abstract: a b s t r a c tThe HypC and HypD maturases are required for the biosynthesis of the Fe(CN) 2 CO cofactor in the large subunit of [NiFe]-hydrogenases. Using infrared spectroscopy we demonstrate that an anaerobically purified, Strep-tagged HypCD complex from Escherichia coli exhibits absorption bands characteristic of diatomic CO and CN À ligands as well as CO 2 . Metal and sulphide analyses revealed that along with the [4Fe-4S] 2+ cluster in HypD, the complex has two additional oxygen-labile Fe ions. We prove t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
90
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(99 citation statements)
references
References 36 publications
7
90
0
2
Order By: Relevance
“…Such a mechanism would ensure that in wild-type cells only a large subunit with a complete NiFe cofactor proceeds along the maturation pathway. After synthesis and insertion of the Fe(CN) 2 CO moiety into the apo-large subunit by the HybG-HypDEF machinery (26,27), nickel insertion occurs (16,19). This step signifies completion of cofactor biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a mechanism would ensure that in wild-type cells only a large subunit with a complete NiFe cofactor proceeds along the maturation pathway. After synthesis and insertion of the Fe(CN) 2 CO moiety into the apo-large subunit by the HybG-HypDEF machinery (26,27), nickel insertion occurs (16,19). This step signifies completion of cofactor biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…A first indication that this C-terminal peptide might be important during enzyme maturation was originally demonstrated for enzymes from both bacterial and archaeal sources (20,21,24). It was subsequently shown that the HypC protein, which is proposed to have an important role in delivering the completed Fe(CN) 2 CO moiety of the active site cofactor to the apo-large subunit (3,(25)(26)(27), interacts with the precursor of the HycE protein, the large subunit of Escherichia coli Hyd-3 (17,18,28). Similar observations were made for Hyd enzymes from Ralstonia eutropha (19,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NiFe(CN) 2 CO biosynthesis requires specific maturation machinery, in which six Hyp proteins (HypA-HypF) play key roles (6,7). Four Hyp proteins (HypC-HypF) are involved in the biosynthesis and incorporation of the Fe(CN) 2 CO group (8)(9)(10)(11)(12)(13)(14)(15). After Fe insertion, HypA and HypB insert the Ni ion into the hydrogenase large subunit (16).…”
mentioning
confidence: 99%
“…Ezek alapján kijelenthető, hogy legalább a HypA, HypB, HypC, HypD, HypE, HypF és egy specifikus endopeptidáz szükséges az érett nagyalegység kialakításához (2. ábra) (Soboh 2012, Bürstel 2012.…”
Section: Hmd Vagy [Fe] Hidrogenázokunclassified